A Case Report: Papular Urticaria Caused by Flea Bites - Rikyanto Rikyanto; Muhammad Amrullah Wahid; Frishia Dida Saraswati; Muhammad Fajarulhuda; Inges Prawita Sari (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2017)
A case reported on 19 years old Javanese woman living in Giwangan District Yogyakarta diagnosed with papular urticaria caused by flea bites. In Indonesia the weather is hotter and more humid during the whole year, it makes flea season might happens anytime. There is a lot of papular urticaria cases with unknown exact causes, it makes this case is interesting because the patient showed that papular urticaria can be caused by Flea bites bring the possible causes for her complains. This report highlights the importance of the biological and epidemiological aspects from the flea.